2008
DOI: 10.1096/fj.07-095398
|View full text |Cite
|
Sign up to set email alerts
|

PYM50028, a novel, orally active, nonpeptide neurotrophic factor inducer, prevents and reverses neuronal damage induced by MPP + in mesencephalic neurons and by MPTP in a mouse model of Parkinson's disease

Abstract: Many experimental data support the enhancement of neurotrophic factors as a means to modify neurodegeneration in Parkinson's disease. However, the translation of this to the clinic has proven problematic. This is likely due to the complex nature of the surgical gene delivery and cell-based approaches adopted to deliver proteinaceous neurotrophic factors to targets within the central nervous system. We investigated the ability of a novel, orally active, nonpeptide neurotrophic factor inducer, PYM50028 (Cogane),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Interestingly, it was suggested that XIB4035, a non-peptidyl small molecule that acts as a GDNF family receptor (GFR)a1 agonist and mimics the neurotrophic effects of GDNF in Neuro-2A cells, might have beneficial effects for the treatment of PD . More recently, the oral administration of PYM50028, a novel non-peptide neurotrophic factor inducer, to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned mice resulted in a significant elevation of striatal GDNF and attenuated the loss of dopaminergic neurons from the substantia nigra (Visanji et al, 2008).…”
Section: Introduction: the Relevance Of Studying The Endogenous Gdnf mentioning
confidence: 99%
“…Interestingly, it was suggested that XIB4035, a non-peptidyl small molecule that acts as a GDNF family receptor (GFR)a1 agonist and mimics the neurotrophic effects of GDNF in Neuro-2A cells, might have beneficial effects for the treatment of PD . More recently, the oral administration of PYM50028, a novel non-peptide neurotrophic factor inducer, to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned mice resulted in a significant elevation of striatal GDNF and attenuated the loss of dopaminergic neurons from the substantia nigra (Visanji et al, 2008).…”
Section: Introduction: the Relevance Of Studying The Endogenous Gdnf mentioning
confidence: 99%
“…Safinamide may be particularly useful if it is able to provide both an antiparkinsonian benefit and a reduction in dyskinesia. [52]. In MPTP-lesioned mice, oral administration of Cogane for 60 days reduced substantia nigra dopamine neuron loss, attenuated reduction of striatal dopamine transporter (DAT), and significantly increased striatal levels of BDNF (511%) and GDNF (297%) [52].…”
Section: Safinamidementioning
confidence: 99%
“…[52]. In MPTP-lesioned mice, oral administration of Cogane for 60 days reduced substantia nigra dopamine neuron loss, attenuated reduction of striatal dopamine transporter (DAT), and significantly increased striatal levels of BDNF (511%) and GDNF (297%) [52]. In MPTPlesioned parkinsonian monkeys, oral administration of Cogane for 18 weeks was associated with a 27% median reduction in parkinsonian disability at 9 weeks and a 43% reduction at 18 weeks [53].…”
Section: Safinamidementioning
confidence: 99%
“…Zhang et al, 2008). Oral administration of smilagenin to MPTP-lesioned mice resulted in a significant elevation of striatal GDNF levels and attenuated the loss of dopaminergic neurons from the substantia nigra (Visanji et al, 2008). Interestingly, smilagenin is now undergoing phase I clinical testing (Aron & Klein, 2011).…”
Section: Inducing Endogenous Gdnf Expression/signalingmentioning
confidence: 99%
“…Zhang et al, 2008). Oral administration of smilagenin to MPTP-lesioned mice elevates striatal GDNF levels and attenuates the loss of dopaminergic neurons (Visanji et al, 2008). Since smilagenin can be taken orally, readily crosses the blood-brain barrier, stimulates GDNF expression, and has neuroprotective effects in the MPTP mouse model of PD, hopefully it is a good candidate for the treatment of PD.…”
Section: Wwwintechopencommentioning
confidence: 99%